ANALISIS EFEKTIVITAS FASILITAS JEMBATAN PENYEBERANGAN ORANG BERDASARKAN KARAKTERISTIK PEJALAN KAKI (STUDI KASUS JPO KARET SUDIRMAN) - Sri Yuniarti; Sri Widayatie; Egit Koeswantoro (FTSP Universitas Jayabaya, 2021)
Several pedestrian bridges in DKI Jakarta are considered to be less attractive to pedestrians for various reasons, including the problem of the distance between the long bridges, the condition of the pedestrian bridges often not meeting standards. In terms of safety and comfort, it is still lacking. The purpose of this study is to analyze the feasibility of JPO Karet Sudirman, determine pedestrian characteristics in terms of volume, pedestrian speed and traffic volume, and analyze the service level (LOS) of Sudirman Karet JPO. The data or information used are primary data obtained from direct field surveys and secondary data obtained from the DKI Jakarta Province Bina Marga Office. After data collection, data processing and data analysis were carried out. The data analysis method used is quantitative analysis method with processing in Microsoft Excel. To obtain research data, a direct observation / survey method was used at the research location. The research survey deals with physical data collection for pedestrian bridges, surveying the volume of vehicle and pedestrian traffic. The results of the calculation are 60% have met the standards of Pedestrian Bridge Planning Procedures for Urban Pedestrians (1995) and 40% do not meet the standards. The volume of pedestrian crossing at JPO Karet Sudirman for 3 days of observation was 1,218 people with an average of 406 people / day. The speed of pedestrians has the highest average speed in 3 days of observation of 64.18 m / minute. The volume of vehicle traffic on Jalan Jendral Sudirman, South Jakarta is 86,557 smp. Based on the average speed of pedestrians, the service level of Sudirman Karet JPO is in the LOS E category with a percentage of 100%. Based on the pedestrian module, the service level of the Sudirman Karet JPO bridge has the LOS B category with a percentage of 55.56%. While the percentage of 44.44% has the LOS A category. Based on the pedestrian flow, the service level of Sudirman Karet JPO has a LOS A category value with a percentage of 100%.